Sustainability of Micro Business Actors during the COVID-19 Pandemic - Yohanes Susanto; Djatmiko Noviantoro; Sari Sakarina; Yusro Hakimah; Irwan Pancasila (Emerging Science Journal, 2022)
This study aims to investigate the effect of leadership, business motivation, and compensation during the Covid-19 pandemic on business existence. This study was conducted in a traditional market in Lubuklinggau City, South Sumatra, Indonesia, with a population of 120 respondents from 1200 micro-enterprises. The validity and reliability tests of 36 samples were conducted using SPSS statistics and inferential analysis using the Amos 8.8 Structural Equation Model (SEM). It was found that leadership has a significant effect on business existence by 0.83, compensation has an effect on business existence by 0.17, and business motivation also affects business existence by 0.24. An important finding from this study is that these three variables together affect the existence of businesses during the Covid-19 pandemic. However, the leadership factor of microbusiness actors is more dominant in influencing the business's existence. Implementing awareness-based health protocols will also have a positive impact on tackling the Covid-19 pandemic. In addition, entrepreneurs can also continue to run their businesses and can foster economic stability, especially in traditional markets. Doi: 10.28991/esj-2022-SPER-020 Full Text: PDF